Optimalisasi Kompetensi Guru dalam Integrasi Teknologi Pembelajaran melalui Professional Learning Community Berbasis Sekolah - Asmawati, Asmawati; Sahidin, Sahidin; Yunarzat, Ersyanda; Saharuddin, Saharuddin; Hamsah, Hamsah; Baso, La; Nasir, Nasir (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2026)
This study examines the role of a school-based learning community in strengthening teachers’ competencies in educational technology integration in a public lower secondary school located in an urban, resource-constrained educational setting. The school is characterized by high teacher participation in collaborative professional development initiatives aimed at supporting digital transformation. A mixed-methods approach with a sequential explanatory design was employed to obtain a comprehensive understanding of how collaborative structures contribute to teacher competency development. Quantitative data were collected through a survey administered to 21 active teacher members of the learning community. Qualitative data were gathered through in-depth interviews and classroom observations and analyzed using thematic analysis. The findings reveal that technology integration remains influenced by contextual constraints, including limited digital literacy, infrastructure limitations, workload pressures, and policy support challenges. The learning community operates as a Professional Learning Community (PLC), facilitating collaborative inquiry, reflective dialogue, peer support, and structured professional learning activities. Participation in the community appears to support the development of teachers’ competencies within the Technological Pedagogical Content Knowledge (TPACK) framework, particularly in integrating technology with pedagogy and subject content.